Integrity, use and care of long-lasting insecticidal nets in Kirinyaga County, Kenya - Mary Nyangi; Elizabeth Kigondu; Beatrice Irungu; Margaret Nganga; Anthony Gachanja; Martin Murigi; Ruth Nyangacha; Erastus Muniu; Luna Kamau; Jeremiah Gathirwa (BMC, 2021)
Abstract Background Vector control is an essential component in prevention and control of malaria in malaria endemic areas. Insecticide treated nets is one of the standard tools recommended for malaria vector control. The objective of the study was to determine physical integrity and insecticidal potency of long-lasting insecticidal nets (LLINs) used in control of malaria vector in Kirinyaga County, Kenya. Method The study targeted households in an area which had received LLINs during mass net distribution in 2016 from Ministry of Health. A total of 420 households were sampled using systematic sampling method, where the household heads consented to participate in the study. A semi-structured questionnaire was administered to assess care and use while physical examination was used to determine integrity. Chemical concentration was determined by gas chromatography mass spectroscopy (GC-MS). Data analysis was done using Statistical Package for Social Sciences (SPSS) version 19. Results After 18 months of use, 96.9% (95% CI: 95.2-98.6%) of the distributed nets were still available. Regarding net utilization, 94.1% of household heads reported sleeping under an LLIN the previous night. After physical examination, 49.9% (95% CI: 43-52.8%) of the bed nets had at least one hole. The median number of holes of any size was 2[interquartile range (IQR) 1-4], and most holes were located on the lower part of the nets, [median 3 (IQR 2-5)]. Only 15% of the nets with holes had been repaired. The median concentration for α-cypermethrin was 7.15 mg/m2 (IQR 4.25-15.31) and 0.00 mg/g (IQR 0.00-1.99) for permethrin. Based on pHI, Chi-square test varied significantly with the manufacturer (X (6, N = 389) = 29.14, p = 0.04). There was no significant difference between nets with different number of washes (X2(2) = 4.55, p = 0.103). Conclusion More than three-quarters of the nets supplied had survived and insecticidal potency was adequate in vector control. Standard procedure for field evaluation of surface insecticidal content available to a mosquito after landing on a net to rest is recommended.